Diversity of marsupial frogs (Anura: Hemiphractidae: Gastrotheca) in the northern Cordillera Central, Peru, with the descriptions of two new species - Duellman, William E.; Duellman, William E.; P. J. Venegas,; P. J. Venegas, (Phyllomedusa, 2017)
Two new species of Gastrotheca are represented by adult females, genomic data of these are included in a phylogenetic analysis, whereby they are placed in the northern clade of the subgenus Gastrotheca. One new species, G. spectabilis, is unique within the genus in having a color pattern consisting of white labial, rostral, and canthal stripes. The second new species, G. oresbios, has a dorsal color pattern of dark paravertebral markings and canthal stripe, but no pale labial stripe; thus it resembles G. abdita, which differs by having an inner tarsal fold, a wider interorbital distance, and smooth skin on the dorsum lacking scattered tubercles as in G. oresbios. Of the nine species of Gastrotheca in the northern Cordillera Central, only G. spectabilis, G. ossilaginis, and G. oresbios lack an inner tarsal fold. The nine species of Gastrotheca known from the high elevations in the northern part of the Cordillera Central in northern Peru, only two are members of the subgenus Duellmania that occurs principally north of the Huancabamba Depression. Only one of the nine species of species of Gastrotheca in the northern part of the Cordillera Central is shared with the Cordillera Occidental in Peru, and none of the species is shared with the Ecuadorian ranges of the Andes.
Centro Jambatu - ID 1605